Achieving high efficiency and improved stability in large-area ITO-free perovskite solar cells with thiol-functionalized self-assembled monolayers. Issue 20 (4th May 2016) - Chang, Chih-Yu; Chang, Yu-Chia; Huang, Wen-Kuan; Liao, Wen-Chi; Wang, Hung; Yeh, Chieh; Tsai, Bo-Chou; Huang, Yu-Ching; Tsao, Cheng-Si
Abstract : A promising approach towards highly efficient and stable large-area ITO-free perovskite solar cells is demonstrated by employing thiol-functionalized self-assembled monolayers as interfacial modification layers. Abstract : We report a novel protocol for achieving highly efficient and stable indium-tin-oxide (ITO)-free large-area perovskite solar cells (PeSCs) by introducing thiol-functionalized self-assembled monolayers (SAMs) to modify the interfacial properties of the devices. Two SAM molecules, 3-mercaptopropyltrimethoxysilane (MPTMS) and (11-mercaptoundecyl)trimethylammonium bromide (MUTAB), are employed as the seed layer for an ultrathin Ag transparent electrode and cathode buffer layer (CBL), respectively. Our results indicate that both SAMs can afford admirable interfacial properties. The thiol groups on the MPTMS SAM can interact with the incident Ag atoms, thereby lowering the percolation thickness of the Ag film to 8 nm. The resulting ultrathin Ag film provides several remarkable features for use as the transparent electrode in PeSCs, including a low resistance of ∼6 Ω sq −1, high average transmittance up to ∼78%, and high robustness against solvents and mechanical deformation. In addition to using the MPTMS SAM as the seed layer, the double-end functionalized MUTAB can not only covalently bond to the Ag surface for SAM formation, but also induce the formation of favorable interfacial dipoles to turn a high work-function (WF) Ag electrode into an efficient low-WF electrode. With these desired interfacial properties, the resulting devices deliver a power conversion efficiency (PCE) up to 16.2%. Notably, a high PCE up to ∼16% can be secured for large-area devices (1.2 cm 2 ) with a SAM-modified ultrathin Ag electrode, which represents the highest performance ever reported for PeSCs with similar active areas. More significantly, the resulting devices also possess good ambient stability without the need for rigorous encapsulation.